2006
DOI: 10.1143/jjap.45.279
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscopy Investigation of Local Atomic Environment of Nitrogen inside Voids Formed at GaN/Sapphire Interface

Abstract: The interrupter technique, the simplest method for measuring airflow resistance (R int ) is particularly valuable under field conditions. We investigate whether during tidal breathing, variations in the flow at which interruption occurs contribute to variability of results. Using a portable device with mouthpiece, sets of 10 measurements of R int (R int,mo ) were made in inspiration and expiration at 0.05 l s −1 intervals from 0.1 up to 0.9 l s −1 flow in 22 normal adults, 11 children (5-9 years) and 12 COPD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…These defects are observed for the first time by HRXT, and their origin is believed to be due to the lift-off process of the GaN films from the sapphire substrates or some other growth-related interface defects. The TEM studies by Matsubara and Shoda [18] and some others have attributed similar voids to the escape of nitrogen creating voids in the freestanding GaN. During the HVPE growth of GaN on sapphire, it is possible that there is some nitrogen trapped by dangling bonds between the GaN epilayers and the substrate, which are broken in the lift-off process and nitrogen escapes from the films.…”
Section: B High-resolution X-ray Topographymentioning
confidence: 92%
“…These defects are observed for the first time by HRXT, and their origin is believed to be due to the lift-off process of the GaN films from the sapphire substrates or some other growth-related interface defects. The TEM studies by Matsubara and Shoda [18] and some others have attributed similar voids to the escape of nitrogen creating voids in the freestanding GaN. During the HVPE growth of GaN on sapphire, it is possible that there is some nitrogen trapped by dangling bonds between the GaN epilayers and the substrate, which are broken in the lift-off process and nitrogen escapes from the films.…”
Section: B High-resolution X-ray Topographymentioning
confidence: 92%
“…The background-subtracted N-K edge peaks were integrated in the energy range between 398 and 448 eV. On the assumption of single scattering and that the bubble is spherical with a diameter d B ~ 20 nm, the density of the nitrogen was estimated to be 1.4 ± 0.3 g/cm 3 , which corresponds to a gas pressure of ~ 3 GPa at 300 K according to a N 2 pressure -density isotherm calculated by Strak et al, 34 or to ~ 2.8 GPa according to a volumepressure diagram for N 2 determined by Mills et al 35 Bubbles with higher densities of (probably solid) nitrogen have been found in sapphire close to a GaN/sapphire interface by Matsubara et al, 36 due to nitridation of the surface. Our pressure estimate is simplified, as it does not consider differences in scattering cross-section between the bubble and the GaN or the unknown temperature of the bubble resulting from the large thermal conductivity difference between nitrogen gas and the GaN host.…”
mentioning
confidence: 93%
“…[30][31][32] Most of them were done in a semi-quantitative way based on the variation of the N-K edge intensity over the nitride matrix and over the pore. [30][31] Indeed, the quantification of the nitrogen density inside small pores is a more challenging problem than for helium.…”
mentioning
confidence: 99%
“…[30][31][32] Most of them were done in a semi-quantitative way based on the variation of the N-K edge intensity over the nitride matrix and over the pore. [30][31] Indeed, the quantification of the nitrogen density inside small pores is a more challenging problem than for helium. The main reason is that the N-K edge position is quite far from the elastic peak and due to the limited dynamical range of the CCD detectors, the low-loss (LL) and core-loss (CL) energy range have to be recorded separately, with different dwell times.…”
mentioning
confidence: 99%